1998
DOI: 10.1093/carcin/19.12.2107
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis is an early event in the development of chemically induced skin tumors

Abstract: In this study we have analyzed the vascular response induced in the two-stage carcinogenesis model in SENCAR mice. The role of angiogenesis has not been explored in this model, which is the paradigm of multistage carcinogenesis and a model for neoplastic lesions derived from exophytic premalignant lesions (e.g. colon carcinoma, bladder papilloma). We investigated if angiogenesis is involved in the formation of papillomas and in the progression from papilloma to carcinoma. To this end we analyzed the vasculatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
49
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 37 publications
12
49
1
1
Order By: Relevance
“…The causal role of angiogenesis in cancer has been assessed in vivo using animal models, including both traditional tumor transplants and mouse models of multistage carcinogenesis. From the latter, it is thought that neovascularization is first activated by an 'angiogenic switch' during premalignant phases of carcinogenesis, before tumors emerge (Folkman et al, 1989;Hanahan and Folkman, 1996;Bolontrade et al, 1998;Huss et al, 2001). Using the 3LL transplantation model, we found that S-Eng þ mice exhibit a deficient angiogenic phenotype leading to retardation of tumor growth.…”
Section: Discussionmentioning
confidence: 87%
“…The causal role of angiogenesis in cancer has been assessed in vivo using animal models, including both traditional tumor transplants and mouse models of multistage carcinogenesis. From the latter, it is thought that neovascularization is first activated by an 'angiogenic switch' during premalignant phases of carcinogenesis, before tumors emerge (Folkman et al, 1989;Hanahan and Folkman, 1996;Bolontrade et al, 1998;Huss et al, 2001). Using the 3LL transplantation model, we found that S-Eng þ mice exhibit a deficient angiogenic phenotype leading to retardation of tumor growth.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, studies have suggested that cyclin D1 can be induced by growth factors and TPA through activation of various signaling pathways including Ras/MAPKs, PI3K/Akt, AP-1, CREB, and NF-nB (62,63). Similarly, reports suggest that VEGF is a potent regulator of angiogenesis and Ha-rasmediated EGFR activation and Akt signaling are involved in the regulation of skin angiogenesis (64,65). In skin carcinogenesis, angiogenesis occurs very early in papilloma development, establishing blood vessel networks as tumors progress (65).…”
Section: Pge 2 Can Induce Cyclin D1 and Vegf In Vivomentioning
confidence: 99%
“…2D). Angiogenesis has been described in benign papillomas induced with 7,12-dimethylbenz[a]anthracene (tumor initiator) and 12-Otetradecanoylphorbol-13-acetate (tumor promoter) in mice (Bolontrade et al, 1998).…”
Section: Beckwith Et Almentioning
confidence: 99%